COMPUTERIZED TRADING SYSTEM OF SALES AT THE EXPO TIP TOP FURNITURE - Dini Sufitri; Don Elsyafitra, SKom (Jurnal Sistem Informasi, 2000)
This writing is intended to help solve business problems on a trade sale (UD) Tip Top Furniture Expo in order to more effectively and efficiently, especially in reducing kerangkapan data, giving the right information, fast and reliable. In this system the author uses Visual Basic 6.0 nMicrosoft. by using a computerized system of cash sales in a bed at UD Tip Top Furniture Expo, has advantages such as speed of obtaining the information, accuracy of data in the sense that there are no data that overlap and can reduce errors that occur in the sales process until the publication of the report.